In vitro shoot regeneration of Stereospermum suaveolens DC. using cotyledonary node and nodal explants - Trivedi, Darshini R; Joshi, Aruna G (Plant Tissue Culture and Biotechnology, 2015)
The cotyledonary node and nodal explants Stereospermum suaveolens DC. were cultured on Woody Plant medium (WPM) supplemented with individual BAP 2?25 ?M), Kn (2?25 ?M) and TDZ (0.1?2 ?M. Observations revealed that in both cotyledonary node and nodal explants, lower concentrations of cytokinins (BAP/Kn/TDZ) were effective in inducing proliferation response. The axillary bud of both the explants proliferated into single shoots which were further subcultured on fresh medium with respective concentrations for shoot multiplication. It was observed that multiple shoots developed only in presence of Kn (8 ?M) in both the explants but the shoots developed from nodal explants were strong and healthy with average shoot number reaching to 3.8 ± 0.6 and length 5.4 ± 0.4 cm by the end of third passage. Rooting (100%) was achieved in microshoots when transferred to half strength WPM liquid medium supplemented with IBA (2 ?M). The plantlets were transferred to different substrates for acclimatization. Plant Tissue Cult. & Biotech. 24(2): 235-246, 2014 (December